Synthesis, in-silico Studies and Evaluation of Anticancer Activity of Some Novel Benzothiazole Substituted 4-Thiazolidinones - Shetty, Chaithra Raju; Bhat, Katte Ishwar; Kumar, Abhishek; Kumar, Pankaj; Krishnamurthy, Praveen Thaggikuppe; Merugumolu, Vijay Kumar (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Cancer is one of the leading diseases associated with the high degree of mortality. In current scenario chemotherapy is the major treatment for cancer and it still has few limitations. The continuous seek for highly effective and safe anticancer agents is the one of the major goal for medicinal chemists. Objectives: In the present work, the hybrid molecule i.e benzothiazole substituted 4-thiazolidinone has been synthesized and evaluated for anticancer activity. Methods: A series of novel benzothiazole substituted 4-thiazolidinone derivatives were synthesized by reacting 2-amino-6-methyl benzothiazole with aromatic aldehydes in alcoholic media, resulting schiff bases are made to react with thioglycolic acid in dioxane. Characterization of synthesized compounds were done by IR, 1H NMR, Mass spectroscopy. In silico studies with molecular docking was performed for the synthesized derivatives by taking proteins from PDB i.e VEGFR-2 kinase and Human thymidylate synthase (PDB ID:2QU5 and 5HS3) as the targets. Results and Discussion: Based on the docking score, best four compounds were selected and screened for in-vitro anticancer activity. From the in-vitro data, finally one potential molecule was selected and evaluated for in-vivo cytotoxic activity. Conclusion: All 4 screened derivatives were found to show good cytotoxic activity, out of which P14 can be considered as promising molecule.
Keywords: Benzothiazole; 4-Thiazolidinone; Anticancer; In silico; Docking